INCOME ANALYSIS OF AGROFORESTRIC SYSTEMS IN IUPHHK-HTI PT. SUMATERA ALAM ANUGERAH, MUARA ENIM DISTRICT, SOUTH SUMATERA PROVINCE - Helida, Asvic; Hidayat, Yayat; Soleha, Okta Sabrina; Syachroni, Sasua Hustati (Universitas Muhammadiyah Palembang, 2021)
Agroforestry is a land management system that may be offered in overcoming the effects of land use and also to overcome food problems. PT. Sumatera Alam Anugerah is one of the holders of IUPHHK-HTI located in Gelumbang District, Muara Enim Regency, South Sumatra Province. To improve the welfare of PT. Sumatera Alam Anugerah is allowed to use land through ansystem agroforestry. The purpose of this study was to determine the benefits of agroforestry and development and the economic conditions of workers of PT. Sumatera Alam Anugerah from activities agroforestry. The method used is a qualitative approach through desk evolution, interviews and Focus Group Discussion (FGD). The results of the study show the social and economic conditions of the workers of PT. Sumatra Nature Award is classified as low because of the education of workers at PT. SAA is a majority of elementary school graduates. Based on the results of the Focus Group Discussion with the existence of system agroforestry at PT. SAA makes workers have permanent producers. Agroforestry is useful to improve the economy of the community besides it can also increase soil fertility.